The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0034-70942002000400014
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflamatórios não esteróides inibidores da ciclooxigenase-2 (COX-2): aspectos atuais

Abstract: RESUMO Backgrounds and Objectives -Due to the high incidence of N S A I D -r e l a t e d s i d e -e f f e c t s , t h e d i s c o v e r y o f t w o cycloxygenase isoforms, classified as: COX-1 or constitutive and COX-2 or inductive, has formulated the paradigm that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
15

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 40 publications
0
14
0
15
Order By: Relevance
“…After this, AA is catalyzed in prostaglandin E2 (PGE 2 ) by ciclooxigenase-2 (COX-2) enzyme. PGE 2 is involved in pain and fever (Kummer & Coelho 2002).…”
Section: Introductionmentioning
confidence: 99%
“…After this, AA is catalyzed in prostaglandin E2 (PGE 2 ) by ciclooxigenase-2 (COX-2) enzyme. PGE 2 is involved in pain and fever (Kummer & Coelho 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Destaca-se que na inflamação aguda duas fases são identificadas: a primeira, detectada em torno de uma hora, chamada de fase rápida, marcada pela liberação de histamina, serotonina e bradicinina; e a segunda, chamada de tardia (1-6 h), em que mediadores como as cininas e prostaglandinas são liberados após duas e três horas, respectivamente, as últimas resultando da ativação da ciclo-oxigenase 2 (COX-2) (Bispo et al, 2000;Silva et al,2005). Considerando que qualquer substância que cause inibição ou redução da ação da carragenina é considerada como tendo ação antiinflamatória (Kummer & Coelho, 2002), os resultados aqui encontrados demonstrando que o extrato aquoso da Amburana cearensis produziu redução do edema induzido pelo flogógeno a partir da segunda hora de administração, evidenciam que os constituintes ativos presentes nas sementes dessa espécie apresentam atividade antiinflamatória e que atuam na fase tardia da inflamação. Como visto (Tabela 2), o aumento da liberação da medula óssea de neutrófilos imaturos (bastões) para o sangue ocorre quando aumenta a demanda funcional de neutrófilos para os tecidos ou em casos de leucemias mielógenas ou mielomonocíticas agudas ou crônicas.…”
Section: Discussionunclassified
“…In a different study with health professionals, it was observed that 50% of respondents stated giving priority to hypertension during medical history; however, these same professionals have reported not knowing pharmacological changes between NSAIDs and antihypertensive drugs 14 . This is of paramount importance since the literature has already described the interactions between NSAIDs and selective COX-2 inhibitors, beta-blockers, diuretics and other anti-hypertensive drugs 1,2,19 . The fact that physical therapists do not know how to adequately use these drugs or their contraindications and potential side effects, makes it mandatory that these professionals have further knowledge about current NSAIDs legislation.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs have been object of concerns and several studies carried out worldwide in the medical area, emphasizing issues regarding their potential adverse reactions, prescription standards and the influence of advertising on their choice 1,2 . According to the Code of Professional Ethics in Physical Therapy and Occupational Therapy, approved by the Resolution Coffito-10, from July 03, 1978, physical therapists are forbidden to prescribe drugs.…”
Section: Introductionmentioning
confidence: 99%